Development of transomental hernia shortly after laparoscopic colonic surgery: a case report - Takahiro Haruna; Akihisa Matsuda; Michihiro Koizumi; Takeshi Yamada; Seiichi Shinji; Yasuyuki Yokoyama; Goro Takahashi; Masahiro Hotta; Takuma Iwai; Keisuke Hara; Kohki Takeda; Hiroshi Yoshida (Surgical Case Reports)
Abstract Background A transomental hernia is defined as bowel invagination into an abnormal hiatus of the omentum. It is a rare type of internal hernia that is sometimes lethal. We herein report a case of a transomental hernia developing shortly after laparoscopic sigmoidectomy. Case presentation A 71-year-old man underwent laparoscopic sigmoidectomy. He was admitted to our hospital because of abdominal pain and nausea on postoperative day 12. Laboratory investigation showed increased levels of inflammatory markers. Abdominal computed tomography showed a closed loop and mesenteric edema of the small intestine with ascites. We performed an emergency operation under the diagnosis of strangulated bowel obstruction. Operative findings showed internal herniation of strangulated ileal loops through a defect of the omentum with hemorrhagic ascites. The incarcerated small bowel was resected and reconstructed because the ischemic change was irreversible after the reduction. We partially resected the omentum that had formed the defect. The patient’s postoperative progress was good, and he was discharged on postoperative day 8. Conclusions Almost all internal hernias after intestinal surgery are mesenteric hernias; however, we should bear in mind that the more lethal transomental hernia is also possible. Therefore, immediate surgical exploration should be performed in a timely manner for internal hernias, especially for patients with early-onset symptoms after laparoscopic intestinal surgery.